2021
DOI: 10.1016/j.psep.2021.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the spatio-temporal characteristics of COVID-19 in mainland China

Abstract: COVID-19 has brought many unfavorable effects on humankind and taken away many lives. Only by understanding it more profoundly and comprehensively can it be soundly defeated. This paper is dedicated to studying the spatial-temporal characteristics of the epidemic development at the provincial-level in mainland China and the civic-level in Hubei Province. Moreover, a correlation analysis on the possible factors that cause the spatial differences in the epidemic's degree is conducted. After completing these work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Based on statistical analysis of the daily time series of meteorological variables, we found that air temperature and surface solar irradiance are inversely correlated (Figure 5) with the confirmed COVID-19 daily new cases (DNCs, r = −0.51, p < 0.01; and r = −0.60; p < 0.01) and deaths (DNDs, r = −0.67, p < 0.01; r = −0.65, p < 0.01), and respectively; the results are comparable with the scientific literature in the field [96], [97], [98].…”
Section: Meteorological Variables and Covid-19supporting
confidence: 83%
See 1 more Smart Citation
“…Based on statistical analysis of the daily time series of meteorological variables, we found that air temperature and surface solar irradiance are inversely correlated (Figure 5) with the confirmed COVID-19 daily new cases (DNCs, r = −0.51, p < 0.01; and r = −0.60; p < 0.01) and deaths (DNDs, r = −0.67, p < 0.01; r = −0.65, p < 0.01), and respectively; the results are comparable with the scientific literature in the field [96], [97], [98].…”
Section: Meteorological Variables and Covid-19supporting
confidence: 83%
“…Based on statistical analysis of the daily time series of meteorological variables, we found that air temperature and surface solar irradiance are inversely correlated (Figure 5) with the confirmed COVID-19 daily new cases (DNCs, r = −0.51, p < 0.01; and r = −0.60; p < 0.01) and deaths (DNDs, r = −0.67, p < 0.01; r = −0.65, p < 0.01), and respectively; the results are comparable with the scientific literature in the field [96][97][98]. Similar results have been reported by some previous studies, which demonstrated an association of weather factors (mostly air temperature, humidity, solar radiation) and COVID-19 transmission in specific regions of the world during different time windows [109], [110].…”
Section: Meteorological Variables and Covid-19supporting
confidence: 83%
“…Like other studies ( Ho et al, 2021 , Bu et al, 2021 , Fang et al, 2021 ), this research demonstrates the high negative impact of outdoor exposure to high ground levels of air pollutants recorded in Bucharest metropolitan city on COVID-19 pandemic incidence and deaths and suggests the urgent need for reduction of air pollutants sources. Lockdown implementation actions are welcome during strong pandemic waves causing air quality improvement ( Rahman et al, 2021 , Han et al, 2023 , Orak and Ozdemir, 2021 , Jin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gao et al (2020) summarized the research on torrential rain in North China in their research progress on the formation mechanism and forecasting methods of heavy rain in China. In response to the heavy rain in North China, Chinese scholars have also carried out research on water vapor conditions, terrain, the underlying surface, and the urban heat island effect (Lei et al, 2020;Ji & Li, 2021;Zhou et al, 2020;. They pointed out that the rainstorms in North China generally occurred under favorable large-scale background conditions, and the rainstorm vapors in North China were mainly contributed by the western Pacific and the South China Sea; the formation of rainstorms was also closely related to the high-and low-level jets.…”
Section: Introductionmentioning
confidence: 99%